Implementasi Internet of Things Berbasis ESP32 dan Blynk untuk Monitoring Mikroklimat Ruang Hunian - M. Faisal Kahfi; Sujono Sujono (JOURNAL SAINS STUDENT RESEARCH, 2026)
In tropical countries such as Indonesia, thermal comfort in residential rooms, especially bedrooms, often receives insufficient attention. High humidity levels can cause discomfort and negatively affect health; however, most homeowners do not have access to simple, accurate measuring instruments. This study intends to develop a microclimate monitoring system based on the Internet of Things (IoT) to measure temperature and humidity in real time. The system was built using an ESP32 microcontroller and a DHT22 sensor, with data transmitted and visualized via the Blynk application. The prototype was tested directly in a residential bedroom to observe actual environmental conditions. The results show that the system operates reliably and provides stable real-time readings. During the ventilation test, room humidity decreased from 86% to 78% after air circulation was activated, while the temperature remained relatively constant at approximately 32°C. The data show that the developed system can assist occupants in understanding indoor environmental conditions and in making well-informed choices regarding room ventilation.